Answer:
x = 1
y = -1
Explanation:
to solve this expression using simultaneous equation, we would say let
y = -8x +7............................................. equation 1
y = x-2............................................equation 2
substitute equation 1 into equation 2
y = x-2............................................equation 2
-8x + 7 = x-2
collect the like terms
7+2 = x + 8x
9 = 9x
divide both sides by 9
x = 1
put the value of x = 1 into equation 1
y = -8x +7............................................. equation 1
y = -8(1) + 7
y = -8 + 7
y = -1